Analisis Kinerja Pengelolaan Pendapatan Asli Daerah di Kabupaten Bone Bolango - Nurshola Yusuf Taha; Julie Abdullah; Saprudin Saprudin; Mohamad Abdul Radjak Masjhur (AKUNTANSI 45, 2025)
In order to implement regional autonomy as described above, local governments are required to be able to recognize sectors that have great potential in encouraging regional development, especially through increasing Local Own-Source Revenue (PAD). PAD maximization can be realized by involving active community participation, especially in terms of tax and levy payments. The analysis technique used is the PAD growth formula and multiple regression analysis test to see the effect of local taxes and levies on PAD revenue. The results showed that based on the results of the calculation of the growth of Local Own-Source Revenue (PAD) in Bone Bolango Regency in the last 5 years, in 2019, there was an increase in PAD growth of 16.33% from the previous year. However, in 2020, there was a decrease in PAD growth of -0.76%. In 2021, there was a significant increase of 20.46%, anpd in 2022, there was an increase in PAD growth, even though it was only 0.45%. Furthermore, in 2023 there was an increase of 39.41%. The statistical test results show that local taxes and local retribution have a positive but insignificant effect on PAD receipts in Bone Bolango Regency.